2014
DOI: 10.1136/bjsports-2013-093398
|View full text |Cite
|
Sign up to set email alerts
|

Fifty-five per cent return to competitive sport following anterior cruciate ligament reconstruction surgery: an updated systematic review and meta-analysis including aspects of physical functioning and contextual factors

Abstract: Background The aim of this study was to update our original systematic review of return to sport rates following anterior cruciate ligament (ACL) reconstruction surgery. Method Electronic databases were searched from April 2010 to November 2013 for articles reporting the number of patients returning to sport following ACL reconstruction surgery. Return to sport rates, physical functioning and contextual data were extracted and combined using random-effects meta-analyses. Data from the original review (articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
954
16
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,021 publications
(1,098 citation statements)
references
References 61 publications
61
954
16
19
Order By: Relevance
“…Taken together, the discordance between patient satisfaction and returning to the pre-injury activity may suggest that imposing a generic definition of successful outcome may be difficult; that success is better defined by the individual. Recent studies have highlighted the potential impact of contextual factors (including social and lifestyle-related factors) on returning to the pre-injury sport, [32][33][34][35][36] and that many people do not return to their pre-injury sport following surgery. 32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the discordance between patient satisfaction and returning to the pre-injury activity may suggest that imposing a generic definition of successful outcome may be difficult; that success is better defined by the individual. Recent studies have highlighted the potential impact of contextual factors (including social and lifestyle-related factors) on returning to the pre-injury sport, [32][33][34][35][36] and that many people do not return to their pre-injury sport following surgery. 32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the potential impact of contextual factors (including social and lifestyle-related factors) on returning to the pre-injury sport, [32][33][34][35][36] and that many people do not return to their pre-injury sport following surgery. 32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee. 37 People may also change their sports participation following surgery on the advice of their treating clinician.…”
Section: Discussionmentioning
confidence: 99%
“…The return-to-sport rates for patients following an ACL reconstruction have been reported to range between 63 and 65% returning to preinjury level of activity with 44-54% returning to competition [34,35]. Altered contralateral hip strategy with limited motion and attenuating forces about the injured knee during gait has been noted in those who did not pass return to sport testing at 6 months [36].…”
Section: Late Post-operative Complicationsmentioning
confidence: 99%
“…10 A recent large review of more than 7500 patients showed a return to competitive sports at 55%. 11 Even more concerning is the possibility that surgical reconstruction of the anterior cruciate ligament, while allowing improved activity as measured by Tegner score, might not provide long-term protection from degenerative change. 12 So although a myriad of authors and researchers continue tremendously important work on surgical techniques, outcomes, and basic science, one must ask whether the layperson really understands the impact of a significant sports injury.…”
mentioning
confidence: 99%